Impact of Soursop Leaf Decoction on Blood Pressure in Individuals with Hypertension: A Systematic Literature Review - Rosalina, Dela Gita; Nurazizah, Tsaniya; Naurah, Ghina Nurjihan; Supriadi, Dedi; Noviati, Elis; Kusumawaty, Jajuk (Genius Journal, 2025)
Introduction: Hypertension remains a leading global health concern, significantly increasing the risk of cardiovascular morbidity and mortality. Interest in natural therapies has grown, including the use of Annona muricata (soursop) leaf decoction, which is hypothesized to exert antihypertensive effects through its bioactive compounds. Objective: This systematic review aims to evaluate the efficacy of Annona muricata leaf decoction in reducing blood pressure among individuals with hypertension. Methods: A comprehensive literature search was conducted across four databases—PubMed, ProQuest, Garuda, and JSTOR—for studies published between 2021 and 2025. Inclusion criteria focused on studies involving hypertensive individuals treated with soursop leaf decoction, with outcomes measured using manual or digital sphygmomanometers. The selection process adhered to PRISMA guidelines. Data extraction and quality appraisal were independently performed by two to three reviewers using the CASP checklist. Extracted data included study characteristics, intervention details, duration, frequency, and delivery methods. Results: A total of 16 studies involving 322 participants were included. Findings consistently demonstrated that soursop leaf decoction significantly reduced both systolic and diastolic blood pressure. The observed antihypertensive effects are attributed to flavonoids and potassium, which contribute to vasodilation. The most effective regimen was consumption twice daily over a 7–8 week period. Conclusion: Annona muricata leaf decoction shows promising potential as an adjunctive, non-pharmacological intervention for managing hypertension. It offers a cost-effective and accessible alternative, especially in low-resource settings. Nonetheless, further clinical trials are needed to determine standardized dosages and assess interactions with conventional antihypertensive medications.